The effect of Tai Chi on plasma homocysteine in 1176 adults: a propensity score matching-based study - Yingchun Gu; Juncai Bai; Yang Li; Ling Han; Dongwei Wang (BMC Cardiovascular Disorders)
Abstract Background Tai Chi is a low-impact form of exercise that involves a series of slow movements that flow together. Increased plasma homocysteine(Hcy) levels are associated with an increased risk of cardiovascular diseases and may be reduced by exercise. This study aimed to compare plasma Hcy levels and the risk of hyperhomocysteinemia in 1,176 adults with and without Tai Chi exercises. Methods This study included 1176 participants from Chenjiagou who adhered to Tai Chi exercise (Tai Chi group, n = 397) and physical examination participants (control group, n = 779). In the Tai Chi group, the type of exercise was 24 simplified forms of Tai Chi, at least 3 times/week for 30–60 min/ time. The median duration of practice for Tai Chi group was 26.5 (11,41) years. Participants in the control group had no regular exercise habits. Baseline data and blood samples were collected from both the groups. Plasma Hcy in the two groups was determined by using the enzyme-linked immunosorbent assay (ELISA) Kit for Hcy. The primary outcome was the difference in Hyc levels between the two groups and the secondary outcome was the effect of Tai Chi on the risk of hyperhomocysteinemia. Propensity score matching(PSM) and other statistical methods were used to balance confounding bias matching and to analyze the effect of Tai Chi on plasma Hcy levels. Results In total, 326 pairs of participants were successfully matched between the Tai Chi group and control group. After matching, the plasma Hcy level of the Tai Chi group was 12.30(10.38, 18.16) umol/L, and that of the control group was 14.69(10.63, 20.29) umol/L, and there was a statistical difference between the two groups (P = 0.008). The prevalence of hyperhomocysteinemia (P<0.001) was significantly lower in the Tai Chi group. Univariate analysis showed that the risk of hyperhomocysteinemia in the control group was 2.37 times higher than that in Tai Chi group. After adjusting for confounding factors, the risk of hyperhomocysteinemia in the control group was 3.67 times higher than that in Tai Chi group. Conclusions Tai Chi exercise may be associated with lower homocysteine levels and is a promising aerobic exercise for Hcy control. Trial registration number ChiCTRl900023059 (Chinese Clinical Trial Registry). The registration date: 2019.5.9.